Effect of foliar spray of GA3 and NAA on sex expression and yield of bitter gourd (Bangladesh Journal of Agricultural Research, 2019)
A field experiment was conducted at the Plant Physiology field of Horticulture Research Center, BARI, Gazipur during two consecutive years of kharif 2014 and 2015 to assess the effect of GA3 and NAA on sex expression, yield and yield components of bitter gourd (Momordica charantia L.) var. BARI Karola-1. Eeleven treatments comprising five concentrations each of gibberellic acid (50, 100, 150, 200 and 300 ppm) and naphthalene acidic acid (50, 100, 150, 200 and 300 ppm) along with distilled water considered as control were evaluated in randomized complete block design with three replications. Gibberellic acid (GA3) and Naphthalene acidic acid (NAA) were sprayed at 4 leaf stage; second spray was done at 35-38 DAS and third spray done at flowering stage. All the treatments improved the flowering and yield characters over control. Foliar spray of NAA @ 150 ppm and 200 ppm was found better in terms of sex expression, yield and yield attributes of bitter gourd as compared to control and other treatments. Spray of NAA @ 150 ppm gave the lowest number of male flowers and the highest number of female flowers thereby produced the lowest sex ratio (male:female). Number of fruits/plant, individual fruit weight and fruit yield/plant were also found maximum from NAA 150 ppm. Maximum fruit yield was recorded with the application of NAA @ 150 ppm. Spraying of NAA @ 150 ppm gave the maximum gross return and net return with the highest BCR of 3.17.Bangladesh J. Agril. Res. 44(2): 281-290, June 2019